A Review of Drug Prevention Program: Implementation in Several Countries - Durrah Athirah Walid; Ahmad Jazimin Jusoh; Siti Zobidah Omar (Peneliti.net, 2021)
Drug prevention programs implemented need to adhere to the policy in achieving the effectiveness to combat drug abuse among adolescents. Further action to improve the prevention program has to be implemented by the authorities to help the nation in countering the drug problems effectively. This study aims to review drug prevention programs implemented in various countries. The method used in this study will be using the four steps developed by Hamzehgardeshi, Shahhosseini, & Gelehkolaee (2015) that include recognizing the research question, searching methods to point out applicable studies, choosing the study, and lastly charting the information, summarizing, and detailing the results. Results show that there are different drug prevention methods implemented in Malaysia, India, China, Sweden, The United States, Brazil, and Australia. Each drug prevention program has its focuses, techniques, and also limitations. In a nutshell, drug prevention programs conducted in any form of methods need to be ensured their effectiveness in achieving desired objectives.